2019
DOI: 10.1007/s40821-019-00128-7
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge leakage, an Achilles’ heel of knowledge sharing

Abstract: In today's knowledge-based economy, organizations are progressively accumulating the knowledge, which they required for innovation, from outside their boundaries. Having accepted the important role of knowledge sharing in innovation performance, it is disappointing to note that the potential harmful impacts of accidental and intentional knowledge leakage on this relationship are still neglected or undeveloped in the literature. Therefore, this study aims to investigate the impact of knowledge sharing and entre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 69 publications
(94 reference statements)
1
11
1
1
Order By: Relevance
“…This study shows that EO has no positive impact on knowledge sharing, which in contrast to a previous study by Vafaei-Zadeh et al (2019). This might be due to the nature of the sampled industries.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This study shows that EO has no positive impact on knowledge sharing, which in contrast to a previous study by Vafaei-Zadeh et al (2019). This might be due to the nature of the sampled industries.…”
Section: Discussioncontrasting
confidence: 99%
“…It is also shown that knowledge sharing has a robust and positive impact on innovation performance, consistent with the literature (Soto-Acosta et al , 2017; Vafaei-Zadeh et al , 2019; Wang and Hu, 2020; Zhao et al , 2021). These results indicate that knowledge sharing is accepted in manufacturing SMEs and they give value to it and consider it as a beneficial practice.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In addition, all the CR values are higher than 0.70, thereby confirming the convergent validity of the measures (Table 3 ). Table 4 displays heterotrait-monotrait ratio of correlations (HTMT .85 ) values below 0.85 thus the acceptable discriminant validity of the measurement model is therefore achieved (Henseler et al 2015 ; Vafaei-Zadeh et al 2019a ).…”
Section: Data Analysis and Resultsmentioning
confidence: 99%